Spirit of the living God: Part 2 - Webb, Barry G.; Moore Theological College Sydney, Aust. (Sydney, Aust. Lancer, 1992)
Includes bibliographical references.
The Exploration series is based on papers presented at the Moore College annual Explorations seminar.
Keywords: Holy Spirit -- theology